2015
DOI: 10.5812/aapm.5(3)2015.22367
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium and Ketamine Gargle and Postoperative Sore Throat

Abstract: Background:Postoperative sore throat is one of the most common complications after endotracheal intubation. Both Ketamine and magnesium can block N-methyl-D-aspartic acid (NMDA) receptors and provide central and local analgesia.Objectives:To compare the effect of magnesium sulfate and ketamine gargle on the incidence and severity of postoperative sore throat.Patients and Methods:A total of 100 patients candidate for emergency acute appendicitis surgery were enrolled in the study. Patients in ketamine group rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 16 publications
2
39
0
Order By: Relevance
“…Mg could be effective in pain relief by exerting the antinociceptive effect46, inhibiting TNF-α47, and modulating hypesthesia and hyperalgesia4849, by blocking the NMDA receptor. The pain relief effect of Mg has been illustrated by several studies in many cases, such as postoperative sore throat50, tourniquet pain51, major non-laparoscopic gastrointestinal surgery52, diabetic neuropathic pain53, cardiac surgery54, and cancer-related neuropathic pain55. The present study also demonstrated that the single-dose IA Mg was effective in pain relief after arthroscopic surgery.…”
Section: Discussionsupporting
confidence: 71%
“…Mg could be effective in pain relief by exerting the antinociceptive effect46, inhibiting TNF-α47, and modulating hypesthesia and hyperalgesia4849, by blocking the NMDA receptor. The pain relief effect of Mg has been illustrated by several studies in many cases, such as postoperative sore throat50, tourniquet pain51, major non-laparoscopic gastrointestinal surgery52, diabetic neuropathic pain53, cardiac surgery54, and cancer-related neuropathic pain55. The present study also demonstrated that the single-dose IA Mg was effective in pain relief after arthroscopic surgery.…”
Section: Discussionsupporting
confidence: 71%
“…Two and 37 studies included patients with an ASA status of I‐III and I‐II, respectively, while the remaining two did not report ASA status . In all, 19 studies detailed the type of surgery, and 32 studies excluded patients who underwent surgeries on the neck or pharynx . The median sample size was 90 (range, 40‐200).…”
Section: Resultsmentioning
confidence: 99%
“…One study compared two doses (50 and 25 mg) . The dose was titrated based on patient body weight in five studies (0.5 mg/kg) . Non‐analgesic comparators included saline (21 studies), water (nine studies), and no pretreatment (two studies).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations